Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 205672 by hardmath last updated on 26/Mar/24

Answered by Berbere last updated on 27/Mar/24

Ω=lim_(n→∞) (1/n)Σ_(k=2) ^n ((√(k(k−1)))/( (√(((√(k−1))+(√k))^2 )))).(Σ_(k=1) ^n (√k))^(−1)   S_1 =Σ_(k=2) ^n ((√(k(k−1)))/( (√(k−1))+k))=Σ_(k=1) ^n ((√(k(k−1)))/( (√(k−1))+(√k)))=Σ_(k=2) ^n (k(√((k−1)))−(k−1)(√k))  =Σ_(k=2) ^n ((k−1)(√(k−1))+(√(k−1))−k(√k)+(√(k)))  =Σ_(k=2) ^n ((k−1)(√(k−1))−k(√k))+Σ_(k=2) ^n ((√k)+(√(k−1)))  =−n(√n)+1+(2Σ_(k=2) ^n (√k)−(√(n−1))+1)  (√(k−1))≤∫_(k−1) ^k (√x)≤(√k)  Σ_(k=2) ^n (√(k−1))≤∫_1 ^n (√x)≤Σ_(k=2) ^n (√k)=S  S−(√n)+1≤(2/3)n(√n)−(2/3)≤S  S∼(2/3)n(√n)  Ω=(1/n)(−n(√n)+2+2S−2(√(n−1+)))/S  Ω∼(1/n)((1/3)n(√n)).((2/3)n(√n))^(−1) =0

Ω=limn1nnk=2k(k1)(k1+k)2.(nk=1k)1S1=nk=2k(k1)k1+k=nk=1k(k1)k1+k=nk=2(k(k1)(k1)k)=nk=2((k1)k1+k1kk+k)=nk=2((k1)k1kk)+nk=2(k+k1)=nn+1+(2nk=2kn1+1)k1k1kxknk=2k11nxnk=2k=SSn+123nn23SS23nnΩ=1n(nn+2+2S2n1+)/SΩ1n(13nn).(23nn)1=0

Commented by hardmath last updated on 27/Mar/24

Thank you dear professor, perfect

Thankyoudearprofessor,perfect

Commented by Berbere last updated on 27/Mar/24

Withe Pleasur

WithePleasur

Terms of Service

Privacy Policy

Contact: info@tinkutara.com